2018
DOI: 10.1002/hed.25128
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with anti‐Sclerostin antibody to stimulate mandibular bone formation

Abstract: Treatment with anti-Scl-Ab significantly increased mandibular bone mass and alveolar height in wild type mice and normalized mandibular bone mass and alveolar height in Ts65Dn mice. The anti-Scl-Ab therapy represents a novel method for increasing mandibular bone formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 39 publications
(112 reference statements)
4
13
0
Order By: Relevance
“…Sclerostin (SOST) is produced by osteocytes and has anti-anabolic effects on bone formation; inhibition of SOST can stimulate bone formation [81]. The SOST secretion was significantly reduced after 7 days in the RPM samples, as compared to the 1 g controls.…”
Section: Discussionmentioning
confidence: 99%
“…Sclerostin (SOST) is produced by osteocytes and has anti-anabolic effects on bone formation; inhibition of SOST can stimulate bone formation [81]. The SOST secretion was significantly reduced after 7 days in the RPM samples, as compared to the 1 g controls.…”
Section: Discussionmentioning
confidence: 99%
“…While this study used an MMP-sensitive PEG hydrogel, other hydrogels that support osteocyte differentiation could readily be infilled into the stiff 3D-printed structure and attain nearphysiological levels of strain in the bone-like layer. Other environmental considerations that are known to influence osteocytes could be studied within this model, which include pH, [89] oxygen tension, [90] drug treatment, [91] hormone levels, [92,93] or inflammatory mediators. [94] Further, this unique model may generate new insights into the osteocyte's role in propagating osteoarthritis progression in response to the changes in fluid flow.…”
Section: Doi: 101002/adhm202001226mentioning
confidence: 99%
“…Regarding periodontal tissues, available data suggest that the efficacy of local administration of sclerostin antibodies remains questionable due to heterogeneous results (Han et al, 2015;Taut et al, 2013). Systemic administration of these agents has showed significant effects on the periodontium, increasing the height of alveolar crest and reducing the distance from CEJ to the alveolar bone crest Tamplen et al, 2018). Furthermore, systemic administration of these antibodies also showed positive effects in animal models of periodontitis, with an increase in bone-mineral apposition rate, bone density, bone-volume fraction, trabecular number and thickness, with a reversion of bone loss due to periodontitis and a reduced CEJ-alveolar crest distance (Chen et al, 2015;Taut et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a local injection of antisclerostin in gingival tissues showed a limited effect on bone healing. Liu et al (2018) and Tamplen et al (2018) evaluated the effects of antisclerostin on the alveolar crest of rats. Both studies found that the systemic administration of the antibody increased the alveolar crest, identified as the reduction of the distance from the CEJ to the top of the alveolar bone crest.…”
Section: Sclerostin and Dkk-1 Antibodiesmentioning
confidence: 99%